PENERAPAN TEKNIK COGNITIVE BEHAVIORAL THERAPY (CBT) UNTUK MENGURANGI PERILAKU KEKERASAN SENIORITAS DI MAS MUQ PAGAR AIR - riska diana; Wanty Khaira; Muslima (IKIP Siliwangi, 2026)
Senior-Junior Violence in boarding school settings has long been normalised as an established part of institutional culture, yet its cumulative impact on junior students’ psychological well-being and academic engagement warrants systematic intervention. This study examined whether Cognitive Behavioral Therapy (CBT) delivered through group guidance could reduce senior-junior violence among students at MAS MUQ Pagar Air. A pre-experimental design with a one group pretest-posttest approach was employed. Participants were seven eleventh-grade students selected through purposive sampling on the basis of their pretest scores, which fell in the moderate-to-high range a 51 item Likert scale instrument (Cronbach’s Alpha = 0,983). Four structured Cognitive Behavioral Therapy (CBT) group sessions were conducted, targeting maladaptif cognitions that sustain domination behavior. Posttest scores for all seven participants shifted from moderate or high categories to low. The Paired Sample t-test yielded a significance value of 0,000 (p ≤ 0,05), with a mean score reduction of 32,70 points, confirming a statistically significant reduction in senior-junior violence behavior. These findings suggest that Cognitive Behavioral Therapy (CBT)-based group guidance is an effective counseling strategy for addressing senior-junior violence and can be integrated into school counseling programs as a structured preventive and corrective measure.